Hypothesis: is yeast a clock model to study the onset of humans aging phenotypes? - Mazzoni, Cristina; Mangiapelo, Eleonora; Palermo, Vanessa; Falcone, Claudio (Frontiers in Oncology, 2012)
In this paper we report the growth and ageing of yeast colonies derived from single cells isolated by micromanipulation and seeded one by one on separated plates to avoid growth interference by surrounding colonies. We named this procedure Clonal Life Span (ClLS), and it could represent a third way of studying ageing together with the Replicative Life Span (RLS) and Chronological Life Span (CLS). In this study we observed over time the formation of cell mass similar to the human “senile warts” (seborrheic keratoses), the skin lesions that often appear after 30 years of life and increase in number and size over the years. We observed that similar signs of ageing appear in yeast colonies after about 27 days of growth and increase during ageing. In this respect we hypothesise to use yeast as a clock to study the onset of human ageing phenotypes.